Russian Language in the Context of Language Policy in the Finno-Ugric Republics of the Russian Federation - E. A. Kondrashkina (Научный диалог, 2019)
The features of the functioning of the Russian language in four Finno-Ugric republics of the Russian Federation, peoples of which entered the Russian state in the XV-XVI centuries, are examined. The consequences of the violent Christianization of the Finno-Ugric peoples are commented. The demographic features of the republics, as well as the current ratio of the Russian and the titular population are characterized. Based on the data on the reduction of the titular population, the question is raised about the possibility of calling these republics Finno-Ugric. The current situation of the Russian and state Finno-Ugric languages in the most important areas of communication is examined in detail. Particular attention is paid to legal acts establishing the status of languages in these republics, namely, laws on languages. Conclusions are drawn about the influence of laws on the linguistic situation and the linguistic competence of the population of the republics. The characteristic types of bilingualism in these regions are determined. The dominant position of the Russian language is stated. It is argued that national languages cannot compete with Russian. A forecast is made on the further development of the situation, in particular, on the functioning of national titular languages and Russian as state language. The novelty of this study is in the combination of historical and modern data, allowing to give a complete picture of the influence of the Russian language on the situation in the republics, to study the reasons for its distribution and dominance in these republics.